Rest‐site selection by fishers (Martes pennanti) in the eastern deciduous forest - Sean W. Gess; E. Hance Ellington; Matthew R. Dzialak; Joseph E. Duchamp; Matthew Lovallo; Jeffrey L. Larkin (Wildlife Society Bulletin)
ABSTRACT Information on fisher (Martes pennanti) resource selection in deciduous forests of eastern North America is limited. We studied resting habitat selection in a fisher population that recolonized predominantly deciduous forest in Pennsylvania, USA, during 2006–2007. We quantified selection by comparing used and randomly selected available sites at 2 spatial scales: the rest structure and at the rest site (area surrounding rest structures). We identified 79 rest structures used by 15 fishers. The most common rest sites were live trees with cavities or broken tops (69%), with black cherry (Prunus serotina), American beech (Fagus grandifolia), and sugar maple (Acer saccharum) accounting for nearly 65% of tree use. Standing dead trees with cavities or broken tops accounted for 17% of rest structures. Ground‐level structures (including burrows, rock piles, and root balls) comprised 14% of observations. Trees selected as rest structures were larger in diameter at breast height (55.3 cm ± 14.9 cm) than were trees at the center of random sites (28.8 cm ± 6.8 cm). Relative to random sites, important components of forest surrounding rest structures included structurally complex forest floors (based on coarse woody debris and rocky ground cover), canopy complexity, and diversity of tree condition class. Maintaining resting habitat for fishers in the eastern deciduous forest can be accomplished through management practices that encourage structurally diverse forests, including retention of coarse woody debris, and variation in tree size and condition. © 2013 The Wildlife Society.